Combustão iniciada por micro-ondas em frascos descartáveis para determinação de níquel e lantânio em nanotubos de carbono por técnicas espectrométricas - Alessio, Keiti Oliveira (2023)
In this work, the use of microwave-induced combustion in disposable vessels (MIC-DV) was proposed for the digestion of carbon nanotubes (CNT) and subsequent determination of Ni and La using colorimetry (for Ni) and inductively coupled plasma optical emission spectrometry (ICP-OES, for La). The results were separated in two manuscripts, where the first one focused on the digestion of CNT by MIC-DV for subsequent colorimetric Ni determination using a smartphone coupled to a USB video camera (UVC) inserted into a camera manufactured in a 3D printer (characterized as a smartphone-based method, SBC). The second manuscript purposes to CNT digestion by MIC-DV for determination of La by ICP-OES. Two CNT samples (multiple wall) were used and acquired in the national market. The reference values were obtained by microwave-assisted digestion (MAD) and microwave-induced combustion (MIC) were used as sample preparation methods. ICP-OES was used as reference detection technique. The best operating conditions for the proposed MIC-DV method were achieved evaluating the influence sample mass, volume and concentration of the absorber solution and pressure applied for the combustion flask. The digests from MIC-DV were compatible with the ICP-OES determination technique for Ni and La. The results obtained in the first manuscript evidenced that the proposed method (MIC-DV/SBC) presented results with good agreement with the reference method, ranging from 96 to 104%. In the second manuscript, the results for La determination by the proposed method (MIC-DV/ICPOES) also showed good agreement with the reference method, ranging from 92 and 99%. The limits of quantification for the determination of Ni (MIC-DV/SBC) and La (MICDV/ICP-OES) were 115 and 3.5 μg g−1 , respectively. In addition, the performance of the proposed methods against the principles of green analytical chemistry (GAC) were evaluated using white analytical chemistry (White Analytical Chemistry - WAC) metric. When compared to the reference methods, it was possible to observe that using the MICDV it is possible to obtain a significant reduction in the volume of waste generated. In addition, the proposed methods stand out for their low cost and excellent analytical performance. Therefore, they can be characterized as a suitable alternative for application in routine analysis, due to the low cost, frequency of analysis, simplicity and, mainly, for being in agreement with the principles of GAC.